SETTLEMENT OF COMPETITIVE ADVANTAGE THROUGH THE ADOPTION OF SYSTEMIC VISION IN TOBACCO PRODUCTIVE CHAIN - Rosalem, Vagner (Perspectivas Contemporâneas, 2009)
The following study expects to show how two companies, acting in the tobacco productive chain, one as a distributor of a national producer and the other as an independent retailer, established a competitive advantage in comparison to other significant competitors in the same productive chain, adopting a systemic vision where a strategic commercial alliance was formed. The methodology used in this paper was the case study, throughout a qualitative research with relevant data of the analyzed companies, before and after the implementation. It was noticed that the systemic vision that provided the alliance implementation increased the profitability of the operations for both companies related to the segment of the focused market, known as popular cigarettes, in addiction, it increased the amount of sales, in benefit of the productive chain these companies belong, as a whole. ADOÇÃO DA VANTAGEM COMPETITIVA ATRAVÉS DA UTILIZAÇÃO DA VISÃO SISTÊMICA NA CADEIA PRODUTIVA DO TABACO RESUMO O seguinte estudo pretende mostrar como duas companhias, atuantes da cadeia produtiva do tabaco, uma como distribuidora de uma produtora nacional e a outra como varejista independente, estabeleceram uma vantagem competitiva em comparação a outro significante competidor da mesma cadeia produtiva, adotando a visão sistêmica onde uma aliança estratégica comercial foi fundada. A metodologia usada em todo este trabalho foi o estudo de caso, com recursos da pesquisa qualitativa com base em dados relevantes das companhias analisadas, antes e depois da implantação. Foi notado que a visão sistêmica, que sustentava a implantação da aliança, aumentava a lucratividade das operações para ambas as companhias relacionadas ao segmento de mercado em estudo, conhecido como cigarros populares, além disso, ele aumentou o número de vendas, em benefício à cadeia produtiva destas companhias como um todo.